2015
DOI: 10.1017/s1478951515000139
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory factor analysis of the Frommelt Attitude Toward Care of the Dying Scale (FATCOD–B) among Italian medical students

Abstract: Objective:A steady increase in the number of patients requiring end-of-life care has been observed during the last decades. The assessment of healthcare students' attitudes toward end-of-life care is an important step in their curriculum, as it provides information about their disposition to practice palliative medicine. The Frommelt Attitude Toward Care of the Dying Scale (FATCOD–B) was developed to detect such a disposition, but its psychometric properties are yet to be clearly defined.Method:A convenience s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 28 publications
(50 reference statements)
4
22
0
Order By: Relevance
“…It also has been argued that the FATCOD scale [24] has issues in terms of validity (Box 1) and the low Cronbach's alpha in the present study points to this problem. We have not studied the long-term effects of the education on palliative care, which limits the possibilities for drawing conclusions on the effect for nurses' working life and thus the quality of care for patients at the end of life.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…It also has been argued that the FATCOD scale [24] has issues in terms of validity (Box 1) and the low Cronbach's alpha in the present study points to this problem. We have not studied the long-term effects of the education on palliative care, which limits the possibilities for drawing conclusions on the effect for nurses' working life and thus the quality of care for patients at the end of life.…”
Section: Discussionmentioning
confidence: 60%
“…However, the Cronbach's alpha was low for the two domains in the Swedish version [8]. Critique of the questionnaireThe scale has been shown to measure a two-dimensional construct [8, 24]. It has been found to contain items that could be revised or omitted, and items 10 and 25 in particular are said to be problematic [24].…”
Section: Methodsmentioning
confidence: 99%
“…Some items refer to the emotional burden involved in caring for the dying, some address beliefs about caring for the dying, and others concern care of families. The most frequently proposed factorial solution seems to involve a two-dimensional structure (Nakai et al, 2006; Henoch et al, 2014; Leombruni et al, 2015 a ). This conceptualization was originally proposed by Nakai and colleagues (Nakai et al, 2006), who defined the first dimension as a “positive attitude about caring for the dying patient” and the second as “perception of patient- and family-centered care.”…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, the present authors tested the efficiency of the two-dimensional model using confirmatory factor analysis (CFA), and we also tested the functionality of the items (Leombruni et al, 2015 a ). We found that the scale construct is two-dimensional, but also that its structure is quite weak due to items with poor validity (i.e., high levels of item measurement error).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation